On Some Misconceptions Concerning the Meaning and Nature of ʿUlamāʾ - Abdul Wahid, Siti Nur ‘Alaniah; Wan Abdullah, Wan Suhaimi (Jurnal Usuluddin, 2022)
This article discusses the major views related to the concept of ʿUlamāʾ, specifically on the meaning and the characteristic of ʿUlamāʾ. It analyzes how this concept is understood and propounded by social scientists as if there exist classifications among ʿUlamāʾ, such as traditionalist and contextualist among ʿUlamāʾ. Therein lies an inherent misconception and if left unaddressed, will cause confusion among the people especially the Muslim community. This subsequently, has an impact on the aspect of social expectations of ʿUlamāʾ. This study rejects some of the sociological interpretations on the concept of ʿUlamāʾ and attempts to correct these misconceptions while emphasizing the characteristic of ʿUlamāʾ in accordance with Islamic tradition.